Representasi Calon Bupati Mandailing Natal Pada Pilkada 2024 Dalam Media Mandailing Online - Salwa Azhira; Siti Kholifah (Jayapangus Press, 2026)
This study analyzes Mandailing Online's representation strategy in reporting on two candidate pairs for Regent of Mandailing Natal in the 2024 regional elections, identifies the power relations and ideologies operating behind these discursive practices, and formulates their implications for the local democratic public sphere. The research employs Norman Fairclough's Critical Discourse Analysis (CDA) as a dialectical reasoning framework (2018, 2020), which systematically moves from describing discursive problems to explaining their social causes and advocating for structural change. The data corpus comprises 174 news articles published from September to November 2024, analyzed qualitatively. The findings reveal systematic discourse polarization: Candidate Pair 01 is consistently constructed through a social-organizational capital framework, while Candidate Pair 02 is represented through performative religiosity discourse. This polarization is structurally produced by media ownership networks that are relationally embedded in local political power, resulting in unequal access to public discourse and a narrowing of voters' capacity for independent political judgment. The study concludes that local media operates as an instrument for reproducing political dominance rather than functioning as an autonomous public sphere, making regulatory reform of media ownership and the strengthening of public critical literacy urgent priorities.